2017
DOI: 10.3389/fcimb.2017.00401
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Diabetic and Non-diabetic Human Leukocytic Responses to Different Capsule Types of Klebsiella pneumoniae Responsible for Causing Pyogenic Liver Abscess

Abstract: The major risk factor for Klebsiella liver abscess (KLA) is type 2 diabetes mellitus (DM), but the immunological mechanisms involved in the increased susceptibility are poorly defined. We investigated the responses of neutrophils and peripheral blood mononuclear cells (PBMCs) to hypervirulent Klebsiella pneumoniae (hvKP), the causative agent of KLA. DNA and myeloperoxidase levels were elevated in the plasma of KLA patients compared to uninfected individuals indicating neutrophil activation, but diabetic status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 47 publications
0
20
1
Order By: Relevance
“…Moreover, these patients often undergo surgical interventions, chemotherapy, radiotherapy, and antibiotic therapy; this could negatively influence the gut flora and the immune system and my enhance the risk of ESBL-producing KPLA. Previous studies have reported that diabetes is an independent risk factor for KPLA [33][34][35]. However, in our study, both univariate and multivariate analyses showed that diabetes was not associated with ESBL-producing KPLA.…”
Section: Discussioncontrasting
confidence: 89%
“…Moreover, these patients often undergo surgical interventions, chemotherapy, radiotherapy, and antibiotic therapy; this could negatively influence the gut flora and the immune system and my enhance the risk of ESBL-producing KPLA. Previous studies have reported that diabetes is an independent risk factor for KPLA [33][34][35]. However, in our study, both univariate and multivariate analyses showed that diabetes was not associated with ESBL-producing KPLA.…”
Section: Discussioncontrasting
confidence: 89%
“…Several studies have examined the role of neutrophils during KLA infection (25). Neutrophils have been reported to effectively kill K. pneumoniae via myeloperoxidase and neutrophil elastase, and it has been shown that hvKp isolates were more resistant than cKp isolates to neutrophil phagocytosis and intracellular killing in vitro (26)(27)(28)(29). It was also shown that during K. pneumoniae infection, K1 bacteria were more resistant to intracellular killing after being phagocytosed by neutrophils and that their escape from neutrophils could potentially contribute to dissemination and metastasis of the disease (30).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with diabetes have high susceptibility to K. pneumoniae infections (Yang et al, 2009;Lin et al, 2013c;Lee et al, 2017b). K. pneumoniae strains are more virulent in diabetic mice than in normal ones (Wu and Tsai, 2005).…”
Section: Introductionmentioning
confidence: 99%